Numerical Simulation of Dendrite Motion Fidelity Based on the Interface Capture Method - Bing Zhang; Shijie Zhang; Yu Zhang; Siyu Zhang; Baofeng Zhu; Ri Li (Journal of Engineering)
During alloy solidification, many free grains in the melt have important effects on the final microstructure and composition distributions. In this paper, grain motion is calculated based on an interface tracking method coupled with a cellular automata (CA) method. First, the interface tracking capabilities of the level set, simple linear interface calculation (SLIC), and piecewise linear interface calculation (PLIC) methods are compared, and the fidelity of the three models is explored. Then, the coupling degrees of these three models with the CA method are analyzed. Finally, the PLIC method is used to simulate various behaviors of grain movement and to verify the authenticity of the dendrite motion calculation. The simulation results show that the VOF methods more readily coupled with the CA model than the level set method, and it is more suitable for calculating the motion behaviors of dendrites. Among the VOF methods, the interface reconstructed by the SLIC method is relatively rough and can only calculate objects with simple morphologies. The PLIC method has a fine interface and small error in the calculation of dendrite movement, and it does not significantly impact the subsequent calculations.